A MODEL FOR DEVELOPING STUDENTS’ ARTISTIC AND CREATIVE ABILITIES THROUGH THE FINE AND APPLIED DECORATIVE ARTS OF KARAKALPAKSTAN - Urazimova, T.V. (SCIENCE and SOCIETY, 2026)
The article is devoted to the model of developing students’ artistic and creative abilities based on the fine and decorative-applied arts of Karakalpakstan. Studying fine and decorative arts enriches creative potential, teaches us to combine utilitarian function with artistic function, and shapes individuality. In addition, during the process of teaching decorative and applied arts, an individual develops aesthetic taste, non-standard thinking, observation skills, and self-realization skills through creating functional and beautiful objects.